Modulation of the gut–brain axis via the gut microbiota: a new era in treatment of amyotrophic lateral sclerosis - Hong, Du; Zhang, Chi; Wu, Wenshuo; Lu, Xiaohui; Zhang, Liping (Frontiers in Neurology, 2023)
There are trillions of different microorganisms in the human digestive system. These gut microbes are involved in the digestion of food and its conversion into the nutrients required by the body. In addition, the gut microbiota communicates with other parts of the body to maintain overall health. The connection between the gut microbiota and the brain is known as the gut–brain axis (GBA), and involves connections via the central nervous system (CNS), the enteric nervous system (ENS), and endocrine and immune pathways. The gut microbiota regulates the central nervous system bottom-up through the GBA, which has prompted researchers to pay considerable attention to the potential pathways by which the gut microbiota might play a role in the prevention and treatment of amyotrophic lateral sclerosis (ALS). Studies with animal models of ALS have shown that dysregulation of the gut ecology leads to dysregulation of brain–gut signaling. This, in turn, induces changes in the intestinal barrier, endotoxemia, and systemic inflammation, which contribute to the development of ALS. Through the use of antibiotics, probiotic supplementation, phage therapy, and other methods of inducing changes in the intestinal microbiota that can inhibit inflammation and delay neuronal degeneration, the clinical symptoms of ALS can be alleviated, and the progression of the disease can be delayed. Therefore, the gut microbiota may be a key target for effective management and treatment of ALS.